Stinetinglers 2 eaudiobook 10 more new stories from the master of scary tales. - Stine, R. L. (Stinetinglers, 2023)
From New York Times bestselling author R.L. Stine, the master of horror for young listeners, comes 10 new stories that are sure to leave you shivering. Stine also reads the introduction to each story! Two kids embark on a field trip to the zoo...and stumble upon a creature they never expected to meet. A boy makes a machine that puts kids in charge...but at what cost? A child is sure his new house is haunted...but is it just in his head? And each story comes with a personal introduction from Stine himself. Laced with Stine's signature humor and a hefty dose of nightmarish fun, Stinetinglers 2 is perfect for fans of Scary Stories to Tell in the Dark and Stine's own Goosebumps books who want even more scares. These chilling tales prove that Stine's epic legacy in the horror genre is justly earned. Dive in, and beware: you might be sleeping with the lights on tonight! A Macmillan Audio production from Feiwel & Friends.